Private sector media and digital news - Cornia, A; Sehl, A; Neilsen, R (Reuters Institute for the Study of Journalism, 2016)
Legacy newspapers and broadcasters are investing in innovation to reach new audiences and generate new incomes on digital platforms, but most of their revenues still come from traditional operations. In this report, we examine how 25 different private sector legacy news organisations in six European countries are adapting to an evolving media environment. The analysis is primarily based on 54 interviews conducted with executives, senior managers, and editors at newspapers and commercial broadcasters. Results show that, because of challenging trends in the digital advertising market (the dominant role of large technology companies, the low average revenues per user, and the growing use of ad-blockers), more and more newspapers are moving to various forms of pay models and are exploring alternative sources of revenue (e.g. native advertising and diversification into e-commerce and business-to-business services). Broadcasters have so far invested less in developing digital news as a part of their business.